EFFECT OF 8 WEEKS OF AEROBIC ON BODY COMPOSITION AND BLOOD PRESSURE IN POSTMENOPAUSAL WOMEN - Gholamrezai Shahram; Zali Mina; Shabani Ramin; Hoseini Rastegar (Physical Education of Students, 2014)
Aim: Nowadays increasing blood pressure is the most important risk factor of coronary, cerebral and renal vessel diseases. Epidemiological studies indicate that Physical inactivity adversely affects the blood pressure in postmenopausal women. The purpose of this study was to determine the impact of aerobic on body composition and blood pressure in postmenopausal women. Methods: 20 healthy postmenopausal women with similar age and weight were randomly devided in intervention and control groups. Subjects completed an informed consent form and health history questionnaire. The intervention group was trained in an aerobic exercise program for 8 weeks (3 sessions weekly). Weight, body fat percentage (BF%), body mass index (BMI), waist to hip ratio (WHR), Lean body mass and blood pressure (BP) were measured in the beginning and the end of the study for all of the subjects. Data were analyzed by the Paired t-test and independent t- test. Results: The results showed that BF% , WHR, BMI decreased and Lean body mass increased significantly in training group after 8 weeks training (P0.05). Conclusions: It seems that a period of aerobic training for 8 weeks can be effective as a non-pharmacological treatment strategy for improvement some physical fitness and body composition indexes, blood pressure in postmenopausal women.